المتطلبات اللازمة في إعداد الكتاب المقرر في تعليم اللغة العربية للدارسين الكبار بوصفها لغة ثانية بماليزيا: دراسة وصفية = Al-mutatallabat al-lazimah fi i'dad al-kitab al-muqarrar fi ta'lim al-lughah al-arabiyyah lid-darisin al-kibar bi wasfiya lughah thaniyah fi maliziya: Dirasah wasfiyyah - Osman, Nurulhuda; Sahrir, Muhammad Sabri; Yaakub, Muhamadul Bakir (The Scientific Institute For Advanced Training and Studies, 2016)
A textbook represents a certain syllabus to facilitate the performance of teaching and learning. It is used by scholars, teachers, schools, and educational institutions as a scientific educational material, as it is an important pillar of the educational components in addition to teachers and students. The textbook plays an important role as a mean of education, without textbook there is no knowledge which leads to the development of civilization, and there will be none of scientific and intellectual creativities are to be relied on, or derived information from a book. Looking into the importance of textbook, it requires educational and learning institutions to take into account appropriate textbook for students which is suitable to their level of ages, intellectual, linguistic, cultural and social and educational background. Based on these previous facts, this study aims to investigate the syllabus of teaching Arabic vocabulary as a second language for adult learners in Malaysia, through a descriptive study of a textbook criteria starting from its definitions, specifications, and needed basis of its preparation: psychological, social, linguistic, educational, basic linguistic characteristics and basic characteristics of language skills for this textbook. By the end of this study, it shows that there should be determination of suitable learning goals for teaching adults, with the clarity of the content, methods of presenting topics of lessons in enhancing students 19 understanding, the lessons in the textbook, the questions and assessments, as well as the learning activities in order to evaluate their performance, understanding, and development in using the textbook and discover the strengths and weaknesses in the syllabus. To achieve the goal of adult learning the Arabic language, it also should take into account the syllabus, foundations, characteristics and elements that were presented in this study.